Some considerations about the internal armed conflict and the responsibility of the peruvian State with Human Rights violations. Entrevista al Dr. Salomón Lerner Febres* - Chumberiza Tupac Yupanqui, Mayté Pamela (2016)
The present interview makes a recount of some events that occurred during the internal armed conflict in our country. Also, the interviewer gives his opinion about the position of the Peruvian State regarding the Interamerican Court of Human Rights.